Study of Jaundice in Pregnancy (Global Journal of Medical Research, 2014)
Objective: This study was aimed at determining pregnancy outcome of cases of jaundice in pregnancy over a 6 year period at tertiary care hospital. Methodology: All case records of patients with jaundice in pregnancy over 6 year period from the medical records office of the hospital and analysed. Results: During the 6-year study period, there were 7180 registered deliveries in the hospital, and 30 cases of jaundice in pregnancy were seen, giving an overall incidence of 0.4% or 1 in 239 deliveries. The disease is more commonly seen in younger age group.Parity has no exact relation with the disease.The commonest chief complaints associated with the disease found in this study were nausea, vomiting, high coloured urine, malaise and pruritus. Viral hepatitis was found to the commonest cause, HEV infection being the commonest, and associated with high maternal and perinatal mortality. Second common cause was found to be cholestatic jaundice of pregnancy, followed by acute fatty liver of pregnancy and HELLP syndrome and drug induced jaundice. Conclusion: The disease is associated with high incidence of preterm labour.Main causes of maternal mortality were found to be, coagulation failure, hepatic coma, renal failure, septicemia.